Efficient optical parametric amplification in the thin film lithium niobate waveguides - Yuanqiang Peng; Shunxing Yang; RuiHuan Wu; Weiyi Hong (Scientific Reports)
Abstract Prominent platforms based on thin-film lithium niobate (TFLN) are superior integrated-photonics platforms for efficient optical parametric amplification (OPA), however, previously few studies have been systematically reported the gain-boosting performance of TFLN waveguides compared to bulk LN waveguides. Here, we optimize two TFLN waveguides with dispersion engineering for high-efficiency and ultra-broadband gain of OPA, then report comparative results about the efficient ultra-broadband OPA of TFLN waveguides in the case of low loss, optimized waveguide length and pump power. Note that the efficient ultra-broadband OPA of TFLN waveguides is represented by the peak gain (71.5 dB) covering a wavelength range of more than 160 nm. And the OPA characteristics of optimized TFLN waveguides are investigated, such as power gain coefficient of dB/cm, length gain coefficient of dB/W, and gain bandwidth. Potential of TFLN integrated-photonics platforms with efficient ultra-broadband OPA show no boundary.